Design of a Data Analytics Model for National Health Insurance Scheme - Yange, Terungwa Simon; Soriyan, Hettie Abimbola; Oluoha, O (Journal of Health Informatics in Africa, 2017)
AbstractBackground and Purpose: The need for better and faster decision-making based on data is stronger than ever; and being able to use massive amounts of data is a necessary competitive advantage. This has necessitated the urgent need for a sophisticated data analytics model for the effective transformation of data into actionable information to enhance quality decision-making. For instance, the healthcare domain is faced with unnecessary delays in the processing of the data submitted to the National Health Insurance Scheme (NHIS).Methods: To address this, a data analytics model based on deep learning was designed in this research using unified modelling language.Results: This model is intended to be implemented using Apache Hadoop and MySQL. When implemented, the model will make it easier to consolidate, cleanse, analyse, and publish data, so that all stakeholders will get information that they can act on, in the format they need.Conclusion: Thus, the stakeholders will access the information more easily, which will enable them to plan, evaluate, and collaborate more effectively.Keywords: Hadoop, Deep Learning, Data Analytics, Health Insurance